Evaluation of azole-resistant mycobiota and mycotoxins profile in tea - Simões, Ana Beatriz (2021)
Tea (infusion of the Camellia sinensis leaves) is one of the most common beverages worldwide, namely, black tea and green tea. Fungal contamination of tea by mycotoxins (produced by filamentous fungi such as Aspergillus) confer potential risks to human health and can cause serious diseases. Continued exposure of Camellia Sinensis to fungicides in conventional agricultural can promote the development of azole resistance among fungal species, such as A.fumigatus. Azole resistance limits therapeutic options against fungal diseases (e.g. aspergillosis), representing a threat to public health. Aims of the study: Identify and quantify the mycobiota through microbiological and molecular analysis; characterize the susceptibility profile of fungi to antifungal drugs of the azole group; assess the contamination of tea by mycotoxins; relate the results obtained with the origin (organic or conventional agriculture) and the type of tea packaging (bulk or tea bags).